Parthenolide reduces empty lacunae and osteoclastic bone surface resorption induced by polyethylene particles in a murine calvarial model of peri‐implant osteolysis. Issue 11 (29th May 2015) - Zawawi, Muhamad S. F.; Marino, Victor; Perilli, Egon; Cantley, Melissa D.; Xu, Jiake; Purdue, P. Edward; Dharmapatni, Anak A. S. S. K.; Haynes, David R.; Crotti, Tania N.
Abstract The study aimed to determine the effects of parthenolide (PAR) on bone volume (BV) and bone surface resorption as assessed by live‐animal microcomputed tomography (μCT) and possible osteocyte death as indicated by empty lacunae histologically in polyethylene (PE) particle‐induced calvarial osteolysis in mice. Baseline μCT scans were conducted 7 days preimplantation of 2 × 108 PE particles/mL over the calvariae (day 0). PAR at 1 mg/kg/day was subcutaneously injected on days 0, 4, 7, and 10. At day 14, BV and surface resorption was analyzed with μCT. Calvarial tissue was processed for histomorphometric osteocyte evaluation. Serum was analyzed for type‐1 carboxy‐terminal collagen crosslinks (CTX‐1) and osteoclast associated receptor (OSCAR) levels by ELISA. PE significantly decreased BV (p = 0.0368), increased surface bone resorption area (p = 0.0022), and increased the percentage of empty lacunae (p = 0.0043). Interestingly, PAR significantly reduced the resorption surface area (p = 0.0022) and the percentage of empty osteocyte lacunae (p = 0.0087) in the PE‐calvariae, but it did not affect BV, serum CTX‐1 or OSCAR levels. The ability of PAR to inhibit PE‐induced surface bone erosion may better reflect the in vivo situation, where bone resorption occurs on the surface at the bone‐implant interface and may also be related to the role of osteocytes in this pathology. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3572–3579, 2015.